Osthole Prevents Heart Damage Induced by Diet-Induced Metabolic Syndrome: Role of Fructokinase (KHK) - Fernando E. García-Arroyo; Guillermo Gonzaga-Sánchez; Alejandro Silva-Palacios; Francisco Javier Roldán; María L. Loredo-Mendoza; Yamnia Quetzal Alvarez-Alvarez; Jesus A. de los Santos Coyotl; Kevin A. Vélez Orozco; Edilia Tapia; Horacio Osorio-Alonso; Abraham S. Arellano-Buendía; José L. Sánchez-Gloria; et al. (MDPI AG, 2023)
There is increasing evidence that either ingested or produced fructose may have a role in metabolic syndrome. While not commonly considered a criterion for metabolic syndrome, cardiac hypertrophy is often associated with metabolic syndrome, and its presence carries increased cardiovascular risk. Recently it has been shown that fructose and fructokinase C (KHK) can be induced in cardiac tissue. Here we tested whether diet-induced metabolic syndrome causes heart disease associated with increased fructose content and metabolism and whether it can be prevented with a fructokinase inhibitor (osthole). Male Wistar rats were provided a control diet (C) or high fat/sugar diet for 30 days (MS), with half of the latter group receiving osthol (MS+OT, 40 mg/kg/d). The Western diet increased fructose, uric acid, and triglyceride concentrations in cardiac tissue associated with cardiac hypertrophy, local hypoxia, oxidative stress, and increased activity and expression of KHK in cardiac tissue. Osthole reversed these effects. We conclude that the cardiac changes in metabolic syndrome involve increased fructose content and its metabolism and that blocking fructokinase can provide cardiac benefit through the inhibition of KHK with modulation of hypoxia, oxidative stress, hypertrophy, and fibrosis.